2018
DOI: 10.1016/j.fertnstert.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The use of preimplantation genetic testing for aneuploidy (PGT-A): a committee opinion

Abstract: The value of preimplantation genetic testing for aneuploidy (PGT-A) as a screening test for in vitro fertilization (IVF) patients has yet to be determined. Several studies demonstrate higher birth rates after aneuploidy testing and elective single-embryo transfer (eSET), suggesting the potential for this testing to decrease the risk of multiple gestations, though these studies have important limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(89 citation statements)
references
References 46 publications
1
83
0
Order By: Relevance
“…The concept of selecting euploid embryos for transfer is an attractive proposition in light of the issues mentioned above. Recent implementation of diagnostic techniques allowing comprehensive chromosome screening combined with trophectoderm biopsy at the blastocyst stage, is expected to increase the effectiveness of PGT‐A, but its routine use is still not unanimously recommended . Recent studies have shown that PGT‐A may not improve overall pregnancy outcomes, so the technique remains disputed.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of selecting euploid embryos for transfer is an attractive proposition in light of the issues mentioned above. Recent implementation of diagnostic techniques allowing comprehensive chromosome screening combined with trophectoderm biopsy at the blastocyst stage, is expected to increase the effectiveness of PGT‐A, but its routine use is still not unanimously recommended . Recent studies have shown that PGT‐A may not improve overall pregnancy outcomes, so the technique remains disputed.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, the number of non-essential biopsy cases should be eliminated. This may include reviewing ASRM’s guidance on the use of PGT-A [ 35 ]. Embryos with breached zonae should be isolated and not transferred until more information regarding SARS-CoV-2 is reviewed.…”
Section: Recommendations: Potential Modifications To Reduce the Risksmentioning
confidence: 99%
“…Potentially, the number of non-essential biopsy cases should be eliminated. This may include reviewing ASRM’s guidance on the use of PGT-A [ 35 ].…”
Section: Recommendations: Potential Modifications To Reduce the Risksmentioning
confidence: 99%
“…However, the true impact on the cumulative pregnancy rate is not yet fully known, as some discarded aneuploid embryos do have the potential to give rise to healthy babies . Routine use of PGT‐A in infertility treatment is therefore questioned and a subject of intense discussion …”
Section: Introductionmentioning
confidence: 99%